(untitled) - Ang, Tom (Dorling Kindersley, 2006)
This is the nearest we've come to a digital imaging bible on outdoor photography. Get snap happy with this comprehensive and motivating guide to digital photography. Packed with inspirational images features detailed coverage of the best cameras, equipment and software, as well as jargon-free tips on demystifying the technical elements of taking both digital and conventional photographs. It is suitable for all levels of experience from amateurs to aspiring David Bailey's. You'll get great results every time.
Keywords: Nhiếp ảnh,Chỉnh sửa hình ảnh,Photography,Image processing; Kỹ thuật,Kỹ thuật,Digital techniques,Digital techniques